Advances in Information and Computer Security 10th International Workshop on Security, IWSEC 2015, Nara, Japan, August 26-28, 2015, Proceedings - Tanaka, Keisuke; Suga, Yuji (Security and Cryptology, 2015)
This book constitutes the proceedings of the 10th International Workshop on Security, IWSEC 2015, held in Nara, Japan, in August 2015. The 18 full papers and 3 short papers presented in this volume were carefully reviewed and selected from 58 submissions. They were organized in topical sections named: identity-based encryption; elliptic curve cryptography; factoring; symmetric cryptanalysis; provable security; LWE-based encryption; privacy-preserving and anonymity; secure protocol; systems security; and security in hardware.